Pendampingan Kegiatan Rihlah Ilmiah Madrasah Aliyah Takhassus Al-Qur’an Wonosobo - Robingun Suyud El Syam; Sunaryo Sunaryo; Intan Masruroh Swastika; Firdaus Firdaus (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This article describes the results of the scientific guidance of Madrasah Aliyah Takhassus Al-Qur'an Wonosobo. The mentoring stages are carried out through three strategies: coordination, implementation and evaluation. The activities take the form of field research with data collection through observation, interviews and documentation, then descriptive analysis. The results of the research show that providing scientific guidance to Madrasah Aliyah Takhassus Al-Qur'an Wonosobo to students can foster religious awareness in everyday life. This contributes to an understanding of the importance of scientific spirit by making pilgrimages to the graves of scholars which enables the birth of an attitude of love for science. The conclusion directs readers to important results and how these results fill research gaps, their novelty and contribution as well as their implications for a wider scope